(соs u)⁾= -sin u*u⁾
a) (10cos(10x) ) ⁾ = -10sin(10x) *10 = - 100sin(10x)
b) ( - cos(10x) -45) ⁾ = - sin(10x) *10 +0 = - 10sin(10x)
d) ( - 0,1cos(10x) +41) ⁾ = 0,1sin(10x) *10+0 = sin(10x)
c) ( -0,1cos(10x) ) ⁾ = 0,1 sin(10x) *10 = sin(10x)
подходят с и d
(соs u)⁾= -sin u*u⁾
a) (10cos(10x) ) ⁾ = -10sin(10x) *10 = - 100sin(10x)
b) ( - cos(10x) -45) ⁾ = - sin(10x) *10 +0 = - 10sin(10x)
d) ( - 0,1cos(10x) +41) ⁾ = 0,1sin(10x) *10+0 = sin(10x)
c) ( -0,1cos(10x) ) ⁾ = 0,1 sin(10x) *10 = sin(10x)
подходят с и d